Forecasting the Future: Trends in Population Growth, Rice Consumption and Rice Demand in North Maluku - Ranita Rope; Ekaria (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Food security is critical as consumption and population are growing rapidly. This study aims to predict population growth, rice consumption and rice demand in the province of North Maluku until 2028 used the ARIMA (2,2,0). Secondary data from BPS-Statistics Indonesia were used, covering population, consumption and rice demand from 2013 to 2023. The results indicated that the annual population growth in North Maluku ranges from 21,000 to 24,000. Simultaneously, the annual rice consumption is projected to increase by approximately two to three kilograms per capita. The predictive data revealed that rice demand was projected to increase from 71.37 million kg in 2024 to approximately 79.09 million kg by 2028, primarily stemmed by ongoing population growth and evolving consumption. These results signaled severe challenges in ensuring an adequate food supply, particularly in a region where rice serves as the primary staple food. These findings underlined the urgent need for data-driven policies, capable distribution networks, and crop diversification to guarantee sustainable food security. Moreover, this research has provided a roadmap for more efficient policy decision-making, highlighting the need for the utilization of modern technology in domestic food cultivation and distribution.